2021
DOI: 10.3390/diagnostics11020236
|View full text |Cite
|
Sign up to set email alerts
|

Using Blood Eosinophil Count as a Biomarker to Guide Corticosteroid Treatment for Chronic Obstructive Pulmonary Disease

Abstract: Treating patients hospitalised with acute exacerbations of chronic obstructive pulmonary disease (COPD) usually involves administering systemic corticosteroids. The many unwanted side effects associated with this treatment have led to increased interest in minimising the accumulated corticosteroid dose necessary to treat exacerbations. Studies have shown that short-term treatment with corticosteroids is preferred, and recent trials have shown that biomarkers can be used to further reduce exposure to corticoste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 97 publications
0
5
0
Order By: Relevance
“…The former category of patients tends to exhibit a lower risk profile with a shorter length of hospitalization, reduced morbidity, and a better response to corticosteroid treatment [ 49 ]. In contrast, high YKL-40 individuals may benefit more from treatment with antibiotics instead of systemic corticosteroids [ 50 ], as low eosinophils are associated with a higher prevalence of bacterial exacerbations [ 49 ]. One may hence expect a more severe impairment in the immune response of these patients that is potentially related to immune cell exhaustion and leads to a more severe risk profile and clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The former category of patients tends to exhibit a lower risk profile with a shorter length of hospitalization, reduced morbidity, and a better response to corticosteroid treatment [ 49 ]. In contrast, high YKL-40 individuals may benefit more from treatment with antibiotics instead of systemic corticosteroids [ 50 ], as low eosinophils are associated with a higher prevalence of bacterial exacerbations [ 49 ]. One may hence expect a more severe impairment in the immune response of these patients that is potentially related to immune cell exhaustion and leads to a more severe risk profile and clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…However, because all the patients were prospectively enrolled in the national COPD care program of Taiwan, most data pertaining to the relevant events and other medical details can be traced on the e-cloud system of National Health Insurance in Taiwan. Finally, without randomization and blindness, the present study may include confounding factors, such as the implementation of pulmonary rehabilitation ( Weiner and Weiner, 2006 ), which may affect the inspiratory flow rate; the change of therapeutic strategies or regimens with disease status or with updated guidelines such as serum biomarker directed inhaled corticosteroid treatment ( Sivapalan et al, 2021 ), better treatment of comorbidities by multidiscipline members, which may all affect the outcome of acute exacerbation. In the future, further research involving prospectively randomized control study is necessary to overcome these limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Measuring blood eosinophils has clinical potential for tailoring systemic corticosteroid treatment for COPD acute exacerbations [ 14 ]. Previous trials have shown that eosinophil-guided systemic corticosteroid treatment for acute exacerbation of COPD was non-inferior to standard of care [ 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Blood eosinophils are surrogate markers for predicting the response to steroid treatment in patients with COPD [ 14 ]. The CORTICO-COP trial investigated a biomarker-guided approach to corticosteroid treatment based on daily blood eosinophil count [ 12 ].…”
Section: Introductionmentioning
confidence: 99%